2022
DOI: 10.3390/healthcare10061020
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a New Electronic Health Record System in a University Hospital: The Effect on Reported Medication Errors

Abstract: Closed-loop electronic medication management systems (EMMS) have been seen as a potential technology to prevent medication errors (MEs), although the research on them is still limited. The aim of this paper was to describe the changes in reported MEs in Helsinki University Hospital (HUS) during and after implementing an EPIC-based electronic health record system (APOTTI), with the first features of a closed-loop EMMS. MEs reported from January 2018 to May 2021 were analysed to identify changes in ME trends wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 27 publications
(36 reference statements)
0
37
0
Order By: Relevance
“…This could be due to omission errors in the medication reconciliation process at admission. 12 13 Levkovich 4 reported that clinical pharmacists achieved medication reconciliation rates exceeding 80% in the study hospital within 24 hours of admission, which is exemplary. It is possible that even though medication reconciliation was performed properly, some medication on the list might be intentionally or unintentionally held during the medication management process by the ordering provider.…”
Section: Implications For Practice: Preventing Omission Errorsmentioning
confidence: 89%
See 1 more Smart Citation
“…This could be due to omission errors in the medication reconciliation process at admission. 12 13 Levkovich 4 reported that clinical pharmacists achieved medication reconciliation rates exceeding 80% in the study hospital within 24 hours of admission, which is exemplary. It is possible that even though medication reconciliation was performed properly, some medication on the list might be intentionally or unintentionally held during the medication management process by the ordering provider.…”
Section: Implications For Practice: Preventing Omission Errorsmentioning
confidence: 89%
“…Further information regarding omission errors was not addressed in Levkovich’s4 study. This could be due to omission errors in the medication reconciliation process at admission 12 13. Levkovich4 reported that clinical pharmacists achieved medication reconciliation rates exceeding 80% in the study hospital within 24 hours of admission, which is exemplary.…”
Section: Implications For Practice: Preventing Omission Errorsmentioning
confidence: 95%
“…Part II of the program extends their competence to a more comprehensive level, including, e.g., untreated indications, drug use without indications, interpreting laboratory values, drug use during aging, renal/hepatic diseases, and medications in their own area of specialty. The new EHR system, APOTTI, has promoted pharmacist-led medication reconciliation in several new emergency departments, outpatient clinics, and municipal health centers [ 50 ]. Clinical pharmacists have begun to offer independent appointments for patients where they can receive advice on their medication, medication reconciliations, and medication reviews.…”
Section: Discussionmentioning
confidence: 99%
“…The core of the in-house CMRTP has remained the same since 2021 and provides for 15 clinical pharmacists per year; however, the current in-house CMRTP consists of two modules: Part (I) Pharmacist-Led Medication Reconciliation (MedRec), and Part (II) Comprehensive Medication Review ( Figure 2 and Table 1 ). The pharmacist-led medication reconciliation was integrated into CMRTP in 2020 because the implementation of a new electronic patient record system (EPIC-based APOTTI) increased the need for pharmacist-led medication reconciliation in HUS significantly [ 50 ]. Integrating these two courses made it possible to train more pharmacists simultaneously.…”
Section: The In-house Comprehensive Medication Review Training Progra...mentioning
confidence: 99%
“…The new electronic client and patient record system Apotti (based on the Epic system) was implemented in the Hospital District of Helsinki and Uusimaa (HUS) starting in November 2018 27 28. The city of Vantaa (approximately 238 000 residents) was among the first municipalities to implement Apotti in May 2019.…”
Section: Methods and Analysismentioning
confidence: 99%